2012
DOI: 10.1128/jb.00776-12
|View full text |Cite
|
Sign up to set email alerts
|

cis -Acting Elements That Control Expression of the Master Virulence Regulatory Gene atxA in Bacillus anthracis

Abstract: Transcription of the Bacillus anthracis structural genes for the anthrax toxin proteins and biosynthetic operon for capsule is positively regulated by AtxA, a transcription regulator with unique properties. Consistent with the role of atxA in virulence factor expression, a B. anthracis atxA-null mutant is avirulent in a murine model for anthrax. In culture, multiple signals impact atxA transcript levels, and the timing and steady-state level of atxA expression are critical for optimal toxin and capsule synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 62 publications
0
31
3
Order By: Relevance
“…This effect, however, is seen only under in vitro conditions that do not induce strong toxin production (10). It was recently reported that manipulation of the atxA promoter to overexpress AtxA did not alter virulence in a murine model of infection (49). While this experiment did not directly replicate the unique atxA expression profile found in the loss of ccdA1 and ccdA2, it does raise questions about the relevance of AtxA overexpression.…”
Section: Discussioncontrasting
confidence: 43%
“…This effect, however, is seen only under in vitro conditions that do not induce strong toxin production (10). It was recently reported that manipulation of the atxA promoter to overexpress AtxA did not alter virulence in a murine model of infection (49). While this experiment did not directly replicate the unique atxA expression profile found in the loss of ccdA1 and ccdA2, it does raise questions about the relevance of AtxA overexpression.…”
Section: Discussioncontrasting
confidence: 43%
“…Finally, an unknown additional repressor binds to the atxA promoter at a palindromic sequence from – 13 to + 31 relative to the P1 transcription start site. Deletion of this sequence results in a 15‐fold increase in atxA transcription (Dale et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…In these culture conditions, which are thought to mimic the mammalian host environment, AtxA positively controls transcription of the three structural genes, lef , pagA and cya , for the anthrax toxin proteins, the capsule biosynthetic operon capBCADE , and numerous other genes on the B. anthracis chromosome and plasmids (Bourgogne et al ., ). atxA ‐null mutants are highly attenuated in murine models for anthrax (Dai et al ., ; Dale et al ., ). Thus, this PCVR is viewed as a critical regulator of B. anthracis virulence.…”
Section: Introductionmentioning
confidence: 97%
“…Transcription of atxA is affected by temperature, redox potential, growth phase and the presence of glucose (Dai and Koehler, ; Saile and Koehler, ; Wilson et al ., ; Chiang et al ., ). The transition state regulator AbrB negatively affects atxA expression (Saile and Koehler, ; Strauch et al ., ), and other trans ‐acting regulators have also been implicated in atxA transcription (Chiang et al ., ; Dale et al ., ). Growth of B. anthracis in media containing bicarbonate in elevated levels of atmospheric CO 2 affects AtxA activity post‐transcriptionally (Koehler et al ., ; Sirard et al ., ; Dai et al ., ; Dai and Koehler, ; Hammerstrom et al ., ).…”
Section: Introductionmentioning
confidence: 98%